Assessment of genetic diversity of Cervus albirostris (white-lipped deer) by microsatellite markers. Issue 4 (1st August 2022) - Han, Ruobing; Zhao, Hongnan; Li, Defa; Li, Heping
Abstract: Cervus albirostris (white-lipped deer) is a unique plateau deer in China. In order to conserve the white-lipped deer population and maintain its sustainable development in Liaoyang, China, ten microsatellite markers was used to analyze the genetic diversity of 42 white-lipped deer, an ex-situ conservation population from Yushu (Qinghai) to Liaoyang (Liaoning). The results showed that expected heterozygosity ranged from 0.399 to 0.825 with a mean of 0.6071, while observed heterozygosity varied from 0.081 to 0.692 with a mean of 0.4456. This study contributes to the study of the unique genetic resources in this ex-situ conservation population and provides a perspective for better implementation of ex-situ conservation of white-lipped deer population in Liaoyang, China.